Association of Chronic Spontaneous Urticaria With Anxiety and Depression in Adolescents: A Mediation Analysis - Huang, Yuzhou; Xiao, Yi; Jing, Danrong; Li, Jie; Zhang, Jianglin; Chen, Xiang; Shen, Minxue (Frontiers in Psychiatry, 2021)
Background: Chronic spontaneous urticaria (CSU) is related to psychiatric comorbidities. It is not clear whether the relationship is affected by modifiable factors. Objectives: To investigate whether the effect of CSU on anxiety and depression in adolescents is mediated by the symptoms of itching and sleep disturbance. Methods: Questionnaire survey was conducted among newly enrolled college students. Dermatologists diagnose skin diseases, including CSU, during health examination. Anxiety and depression were measured by the Generalized Anxiety Disorder Scale and Patient Health Questionnaire, respectively. Sleep quality was measured by the Pittsburgh Sleep Quality Index. The symptoms of itching were measured by the numeric rating scale. According to the hypothesis, the mediating effect model was put forward and the structural equation model is used to build the mediation effect model. The mediation effect model was proposed according to the hypothesis and established using a structural equation model. Results: A total of 2,358 students with no history of systemic disease and no pruritus disease (except CSU) were included in the analysis. A total of 393 CSU patients were included, and 1,965 healthy controls were selected based on age and sex matching. CSU was significantly associated with both anxiety and depression when the symptoms of itching and sleep quality were not modeled. A mediation model was proposed as CSU → itching → sleep disturbance → anxiety or depression. Itching and sleep quality mediated 65.4 and 77.6% of CSU's effects on anxiety and depression, respectively, and CSU had no significant direct effect on anxiety or depression in the mediation models. Conclusions: The associations of CSU with anxiety and depression were mediated by the symptoms of itching and sleep disturbance. Effectively reducing the symptoms of itching thereby could increase natural sleep, which can further treat the emotional disorders among patients with CSU.